Selenium participates in the formation of kidney stones by alleviating endoplasmic reticulum stress and apoptosis of renal tubular epithelial cells - Xiaozhe Su; Hongbo Chen; Heng Xiang; Hu Ke; Caitao Dong; Qianlin Song; Jiawei Zhou; Qinhong Jiang; Yunhan Wang; Liang Chen; Sixing Yang (Redox Report)
Objectives: To investigate the role of selenium and selenium-containing proteins in the etiology and pathogenesis of kidney stones.Methods: The HK-2 cell line was subjected to supersaturation oxalate treatment to establish an in vitro model of calcium oxalate kidney stones, while SD rats were administered with ethylene glycol to establish an in vivo model of calcium oxalate kidney stones. qPCR analysis was employed to investigate the alterations in selenoproteins within the models, and subsequently, genes exhibiting significant changes were identified. Subsequently, based on the functions of these genes, their regulatory effects on endoplasmic reticulum stress (ERS) and apoptosis during the disease progression were examined both in HK-2 cells and rat kidneys. Finally, Selenomethionine (SeMet) supplementation was introduced to explore its therapeutic potential for kidney stone management.Results: The involvement of Selenoprotein K in the pathogenesis of calcium oxalate kidney stone disease has been confirmed, exhibiting significant alterations. Manipulation of its expression levels through overexpression and knockdown techniques resulted in a corresponding reduction or increase in oxidative stress, ERS, and apoptosis within renal tubular epithelial cells. SelK regulates ERS and apoptosis by controlling the IRE1-ASK1-JNK pathway. In addition, SeMet treatment, which contains selenium, effectively reduced the levels of oxidative stress, ERS, and apoptosis in vivo and in vitro models, thereby alleviating tubular epithelial cell damage and reducing the formation of kidney stones in experimental rats.Discussion: Selenium is involved in the occurrence and development of kidney stones by regulating oxidative damage to renal tubular epithelial cells. The results suggest that dietary selenium supplementation in daily life may be of great significance for the prevention and treatment of kidney stones.